Anti‐Tumor Effects of Cardiac Glycosides on Human Lung Cancer Cells and Lung Tumorspheres. Issue 9 (10th April 2017) - Kaushik, Vivek; Yakisich, Juan Sebastian; Azad, Neelam; Kulkarni, Yogesh; Venkatadri, Rajkumar; Wright, Clayton; Rojanasakul, Yon; Iyer, Anand Krishnan V.
Abstract : Lung cancer is a leading cause of cancer‐related death in the United States. Although several drugs have been developed that target individual biomarkers, their success has been limited due to intrinsic or acquired resistance for the specific targets of such drugs. A more effective approach is to target multiple pathways that dictate cancer progression. Cardiac glycosides demonstrate such multimodal effects on cancer cell survival, and our aim was to evaluate the effect of two naturally occurring monosaccaridic cardiac glycosides—Convallatoxin and Peruvoside on lung cancer cells. Although both drugs had significant anti‐proliferative effects on H460 and Calu‐3 lung cancer cells, Convallatoxin demonstrated twofold higher activity as compared to Peruvoside using both viability and colony forming assays, suggesting a role for the aglycone region in dictating drug potency. The tumor suppressor p53 was found to be important for action of both drugs—p53‐underexpressing cells were less sensitive as compared to p53‐positive H460 cells. Further, assessment of p53‐underexpressing H460 cells showed that drugs were able to arrest cells in the G0/G1 phase of the cell cycle in a dose‐dependent manner. Both drugs significantly inhibited migration and invasion of cancer cells and decreased the viability of floating tumorspheres. An assessment of intracellular pathways indicated that both drugs were able to modulate proteins that are involved in apoptosis, autophagy, cell cycle, proliferation, and EMT. Our data suggest, a promising role for cardiac glycosides in lung cancer treatment, and provides impetus for further investigation of the anti‐cancer potential of this class of drugs. J. Cell. Physiol. 232: 2497–2507, 2017. © 2016 Wiley Periodicals, Inc. Abstract : The cardiac glycosides convallatoxin and peruvoside exert potent anti‐cancer effects in lung cancer cells. A significant inhibition of cell migration, invasion, and lung tumorsphere formation was observed in response to both drugs.